2019
DOI: 10.1021/acs.inorgchem.9b02866
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Valence-to-Core X-ray Emission Spectroscopy: A Sensitive Probe of Oxo Protonation in Structural Models of the Oxygen-Evolving Complex

Abstract: Calcium is an abundant, nontoxic metal that finds many roles in synthetic and biological systems including the oxygen-evolving complex (OEC) of photosystem II. Characterization methods for calcium centers, however, are underdeveloped compared to those available for transition metals. Valence-to-core X-ray emission spectroscopy (VtC XES) selectively probes the electronic structure of an element’s chemical environment, providing insight that complements the geometric information available from other techniques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 100 publications
0
19
0
Order By: Relevance
“…The VtC XES spectral features have been shown to arise largely from ligand n p and n s molecular orbitals. Hence, both the energies and the intensities of the VtC spectral features depend strongly on ligand identity and, as such, are incredibly useful for determining the identity of coordinated ligands. , To date, very little research on VtC XES of zinc compounds has been reported, although VtC XES of other metals has led to a wide range of discoveries, including the identification of the interstitial carbon in the active site of molybdenum and vanadium nitrogenases, detection of bridging oxygen ligands and assessment of protonation states in an oxygen evolving complex and in related structural models, , and as a means to assess O–O and N–N bond activation. , …”
Section: Introductionmentioning
confidence: 99%
“…The VtC XES spectral features have been shown to arise largely from ligand n p and n s molecular orbitals. Hence, both the energies and the intensities of the VtC spectral features depend strongly on ligand identity and, as such, are incredibly useful for determining the identity of coordinated ligands. , To date, very little research on VtC XES of zinc compounds has been reported, although VtC XES of other metals has led to a wide range of discoveries, including the identification of the interstitial carbon in the active site of molybdenum and vanadium nitrogenases, detection of bridging oxygen ligands and assessment of protonation states in an oxygen evolving complex and in related structural models, , and as a means to assess O–O and N–N bond activation. , …”
Section: Introductionmentioning
confidence: 99%
“…An overestimation of the MO splitting due to oxygen protonation in the DFT calculations has been observed previously in studies of Ca and Mn VtC XES. 41,77 As such, it is likely that the peak broadening that occurs in calculated spectra will be somewhat less apparent in experimental spectra.…”
Section: Theory Of P Kβ Xesmentioning
confidence: 99%
“…In recent years, Kβ X-ray emission spectroscopy (XES) has become a more frequently used technique, with a focus on 3d transition metals. [40][41][42][43][44][45][46] Some work has also been performed on 4d elements, [47][48][49] and sulfur Kβ X-ray emission has been somewhat explored, [50][51][52][53][54] including a study of the protonation state of aqueous sulfate, 55 but very few Kβ XES studies of phosphorus have been reported. 50,[56][57][58] Phosphorus Kβ X-ray emission spectroscopy (XES) has great potential as a probe of phosphorus in both molecular and biological systems, promising rich electronic structural information and compatibility with diverse sample preparations that would augment existing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant synthetic efforts to prepare heterometallic complexes that mimic the OEC in terms of structure and redox state, [37,[45][46][47][48][49][50][51][52][53][54][55][56][57][58] the effect of structural distortions or protonation state on the electronic structure of multimetallic Mn complexes is not well understood, and can be summarized as follows. [59][60][61][62][63] In as eries of dinuclear complexes featuring IV (OH) 2 cores,the antiferromagnetic coupling is strongest in the fully deprotonated form, with successive oxo protonations resulting in weaker antiferromagnetic coupling. [60] Ac omplete shift from ferromagnetic to antiferromagnetic coupling is observed upon asingle protonation of the adamantane-shaped [Mn 4 IV O 6 ] 4+ core.…”
Section: IVmentioning
confidence: 99%